PROBLEMATIC INTERNET USE AND SOCIAL ANXIETY IN LATE ADOLESCENTS SOCIAL MEDIA USERS IN BEKASI CITY - Arinda, Radiva Febrian; Fitriyana, Rika; Afriyenti, Lenny Utama (Politeknik Kesejahteraan Sosial Bandung, 2024)
The phenomenon of problematic internet use is one of the phenomena that is rife in late adolescents. This is an important concern for many researchers, especially regarding excessive internet use, especially in accessing social media. This study aims to determine whether there is a relationship between problematic internet use and social anxiety in late adolescents who use social media in Bekasi City. This study involved 111 late adolescents in the city of Bekasi who actively used social media for 5 hours or more/day. This research is a quantitative research with a correlational type. The sampling technique uses a purposive sampling technique. Data analysis was performed with the correlation technique of Pearson Product Moment using the program SPSS versi 25 for windows. Based on the result of research data analysis the value of corellation coefficient between those two variables is 0,661** with significant degree amount is 0,000, This suggest that there is a a positive relationship between problematic internet use and social anxiety among adolescents. So it can be concluded that the higher the problematic internet use in adolescents, the higher the level of adolescent anxiety.